2017
DOI: 10.1007/s12031-017-0954-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of hsa-miR-6165 in Human Cell Lines and During the NT2 Cell Neural Differentiation Process

Abstract: MicroRNAs are small non-coding RNAs that posttranscriptionally regulate mRNA expression. hsa-miR-6165 which was previously discovered in our group is located in the forth intron of p75NTR gene and its function is still under investigation. As P75NTR has diverse cellular functions, some of the complexity of its function could be attributed to the internally located microRNA. Our analysis revealed that treatment of HCT116 cells with 5-azacytidine promoted differential expression of hsa-miR-6165 from its host gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The bioinformatic analysis results showed that miR-766-3p, miR-6749-3p, and miR-6165 played an important role in these pathways. Hassanlou et al also reported that the overexpression of miR-6165 could downregulate ABLIM-1, PVRL1, and PDK1 target genes, thereby affecting cell cycle progression and inhibiting NT2 neural cell differentiation [52].…”
Section: Discussionmentioning
confidence: 99%
“…The bioinformatic analysis results showed that miR-766-3p, miR-6749-3p, and miR-6165 played an important role in these pathways. Hassanlou et al also reported that the overexpression of miR-6165 could downregulate ABLIM-1, PVRL1, and PDK1 target genes, thereby affecting cell cycle progression and inhibiting NT2 neural cell differentiation [52].…”
Section: Discussionmentioning
confidence: 99%
“…11 14 27 28 The functional role of ABLIM1 was also suggested to be related to the modulation by upstream ncRNAs, such as lncRNA ZNF667-AS1, miR-6165, and miR-129-3p. 13 29 30 The regulatory effect of ABLIM1 on DVT development was further investigated to disclose the potential regulatory mechanism. With the help of online databases, miR-2467-3p was predicted as a direct upstream miRNA of ABLIM1.…”
Section: Discussionmentioning
confidence: 99%
“…The hsa-miR-6165 is another upstream microRNA of ABLIM1 in NT2 neural cells. The hsa-miR-6165 overexpression can downregulate ABLIM1, attenuate NT2 differentiation, and affect the cell cycle and apoptosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%